Burgeoning burden of non-communicable diseases in Nepal: a scoping review. Issue 1 (December 2015) - Mishra, Shiva; Neupane, Dinesh; Bhandari, Parash; Khanal, Vishnu; Kallestrup, Per
Abstract In the last decades, prevalence of non-communicable diseases (NCDs) has escalated in Nepal. This study reviews existing evidence on the burden of non-communicable diseases in Nepal using the framework developed by Arksey and O'Malley for scoping reviews. A total of 110 articles were identified from database searches, and four from additional searches. The titles and abstracts were reviewed using predetermined screening criteria. We limited our search to existing literature in English language and included all studies regardless of year of study. Both observational and interventional studies were included. Studies conducted outside Nepal and studies not reporting prevalence of NCDs were excluded. Additionally, we searched reference lists of included publications. All previous reports of Step Wise Surveillance to NCDs (STEPS Surveys) were included in the review. Finally, a total of 60 articles were included in this review. Limited studies on population-based prevalence of mental illness, chronic respiratory diseases, cardiovascular diseases, and road traffic accidents were found. There were limitations in the studies related to generalizability due to small sample sizes, non-random sampling and lack of studies from certain region of country. Nevertheless, high prevalence of hypertension and diabetes was found. Similarly, hospital-based studies reported high burden of cardiovascular diseases among outpatient contacts. Population-based cancer registries do not exist in Nepal. However, existing studies report 8, 000-10, 000 cancer deaths annually in Nepal. The most common cancer site in males was the lung, followed by the oral cavity and gastric, while the first three in females were cervix uteri, breast and lung. Prevalence of psychiatric morbidity was also high. Despite alarming burden of NCDs, the country's response is weak. Nepal needs to build non-communicable disease programmes with focus on disease prevention and management as well as awareness activities in urban and rural settings at community level.